Honorary Doctorate Dr. Souha Kanj, 15th of October 2020 - Kanj, Souha (Doctor Honoris Causa Series / Faculty of Medicine, Radboud University, 2023)
On 15 October 2020, in the middle of the COVID-19 pandemic, Dr. Souha Kanj received a Radboud honorary doctorate in recognition of her achievements in the field of infection control and prevention, efforts in antimicrobial stewardship, and research on various infectious diseases, particularly antimicrobial resistant (AMR) bacteria. This edition includes the laudatio and the speech of our honorary doctor.Kanj published the first overview of antibiotic resistance in Arab countries and discovered differences between neighboring countries in the epidemiology of antimicrobial resistance. She also developed infection prevention monitoring and education programs for healthcare workers, and private organizations in the Arab world. Thanks to her efforts, Lebanon has signed the WHO pledge for hand hygiene. Kanj is not only commended for her expertise, didactic skills, and contribution to medicine, but also for her resilience and strong belief in making a positive impact, despite the difficult journey she has been through, having studied during the Lebanese civil war and being faced with numerous challenges that hit Lebanon and the region after that.Prof. dr. Heiman Wertheim, head of the clinical microbiology department at Radboud UMC: "Kanj has become a role model and inspiration for female and male physicians and infectious disease trainees in the Middle East and beyond." On 20 October 2022, the day that Radboud University celebrated its 99th anniversary, Dr. Katalin Karikó received a Radboud honorary doctorate in recognition of her scientific contributions to developing mRNA-based vaccines. This edition includes the laudatio of the honorary supervisor and the speech of the honorary doctor.Karikó spent years researching medical applications of mRNA. Her dream was to develop synthetic mRNA and use this to cure cancer, strokes, and influenza. Eventually, after years of toil, rejection, and criticism from colleagues, she and fellow researcher Drew Weissman demonstrated that it is possible to trigger an immune response in the body with mRNA without the body turning against the mRNA itself. With this breakthrough, a new revolutionary technique was born.Thanks to Karikó's scientific work, BioNTech/Pfizer and Moderna were able to develop the current mRNA vaccines against COVID-19. A prime example of the beneficial impact that fundamental research can eventually have on society. Honorary supervisor Floris Rutjes, Professor in Organic Synthesis: "With courage and determination, she pursued her scientific vision for a very long time, and by doing so, she has ultimately made a significant contribution to the fight against viral diseases."